More subjects are required for ventrolateral than dorsolateral prefrontal TMS because of intolerability and potential drop-out - Han, Shuyan (PLoS One, 2019)
Transcranial magnetic stimulation (TMS) of the human lateral prefrontal cortex, particularly the ventral region, often causes considerable discomfort to subjects. To date, in contrast to abundant literature on stimulations to the dorsolateral prefrontal cortex, the ventrolateral prefrontal cortex has been less frequently stimulated, partly because some subjects are intolerable of stimulation to the ventrolateral prefrontal cortex. To predict the additional number of subjects required for the stimulation of the dorsolateral and ventrolateral prefrontal cortices, 20 young healthy subjects reported two evaluation scores: the discomfort caused by TMS and the resulting intolerability to complete the TMS experiments. Single-pulse stimulation (SPS) or theta-burst stimulation (TBS) was administered to the lateral prefrontal cortex. The high-resolution extended 10–20 system was used to provide accurate estimation of the voxelwise scores. The discomfort ratings with the SPS and TBS were relatively higher in the ventrolateral prefrontal cortex than those in the dorsolateral prefrontal cortex. Both the SPS and TBS elicited maximal discomfort at the stimulation position F8. The SPS and TBS to F8 under the standard TMS protocols were intolerable for approximately one half (11 and 10, respectively) of the subjects. The intolerability was further calculated for all voxels in the lateral prefrontal cortex, which enabled us to estimate the additional number of subjects required for specific target areas. These results suggest that prior knowledge of subjects’ discomfort during stimulation of the lateral prefrontal cortex can be of practical use in the experimental planning of the appropriate number of recruited subjects and provide the database for the probability of intolerability that can be used to predict the additional number of subjects.